Recombination rates in admixed individuals identified by ancestry-based inference - Wegmann, Daniel; Kessner, Darren E; Veeramah, Krishna R; Mathias, Rasika A; Nicolae, Dan L; Yanek, Lisa R; Sun, Yan V; Torgerson, Dara G; Rafaels, Nicholas; Mosley, Thomas; Becker, Lewis C; Ruczinski, Ingo; et al. (Nature genetics, 2011)
John Novembre and colleagues present a new approach for constructing recombination maps based on ancestry switch points among individuals. They construct a high-resolution genome-wide recombination map based on admixed African-American and African-Caribbean individuals and compare this to previous recombination maps. Studies of recombination and how it varies depend crucially on accurate recombination maps. We propose a new approach for constructing high-resolution maps of relative recombination rates based on the observation of ancestry switch points among admixed individuals. We show the utility of this approach using simulations and by applying it to SNP genotype data from a sample of 2,565 African Americans and 299 African Caribbeans and detecting several hundred thousand recombination events. Comparison of the inferred map with high-resolution maps from non-admixed populations provides evidence of fine-scale differentiation in recombination rates between populations. Overall, the admixed map is well predicted by the average proportion of admixture and the recombination rate estimates from the source populations. The exceptions to this are in areas surrounding known large chromosomal structural variants, specifically inversions. These results suggest that outside of structurally variable regions, admixture does not substantially disrupt the factors controlling recombination rates in humans.